Способы модернизации щелевых регуляторов расхода жидких сред - Дубовец, А. Н.; Литвиненко, Игорь Иванович; Подустов, Михаил Алексеевич; Литвиненко, Евгения Игоревна (Национальный технический университет "Харьковский политехнический институт", 2015)
Предложен способ модернизации щелевого регулятора уровня, позволяющий исключить влияние плотности жидкости на результаты регулирования, уменьшить порог чувствительности регулятора и погрешность регулирования. Кроме того, исключаются погрешности, вызываемые наличием пены и волнообразования на поверхности жидкости, налипанием на чувствительный элемент регулятора твердой фазы пульп, суспензий. Поплавковый чувствительный элемент регулятора целесообразно заменять чувствительным элементом, состоящим из двух щелей. Щели установлены так, что при заданном уровне жидкости в приемной емкости регулятор расхода Q₁ и Q₂ жидкости из щелей имеют равные значения.

A method is proposed modernization of the slot level control that allows you to eliminate the effect of liquid density on the results of the regulation, to reduce the sensitivity threshold of the regulator and control error. In addition, excludes errors caused by the presence of foam and wave formation on the surface of the liquid sticking on the sensor element controller of the solid phase of slurries, suspensions. Float sensing element of the regulator should be replaced with the sensor element, consisting of two slits. The gap is set so that when a predetermined level of liquid in the receiving tank flow regulator Q₁ and Q₂ of the liquid out of the slits are of equal value. The sensitivity threshold and measurement error slotted regulator liquid medium can be reduced through use of sensitive elements that implement the differential principle, when the output signal of the sensing element is equal to 0 for a given level of liquid medium in the receiving capacity of the regulator, but is opposite in sign of the increment corresponding to the increase and decrease in the level relative to a predetermined value. Float sensing element gap of the liquid flow regulator should be replaced with the sensor element, consisting of two slits in the choice of their parameters in accordance with the requirement.
The ways of modernization of annular flow of liquid media
Keywords: уровнемер; щель; суспензия; пульпа; бункер; патрубок; поплавок; плотность; sensor; air gap; suspension; slurry; hopper; tube; float; density